Cognitive dysfunctions in patients with bipolar disorder: A comparative study from Western Rajasthan - Ankit Awasthi; Arpit Koolwal; Nikita Dhaka; Ghanshyam Das Koolwal; Sanjay Gehlot (Asian Journal of Medical Research, 2020)
Background: Cognitive dysfunction is an established entity in bipolar disorder. The affected individuals exhibit wide-ranging deficits involving multiple domains of cognitive functioning. These deficits are associated with poor functional outcome and residual disability in patients. A substantial literature exists globally on cognition in bipolar disorder; however, few studies have been carried out on this subject in India and    in Rajasthan. The aim of the study is to compare cognitive functions of bipolar disorder patients and healthy control subjects. Subjects and Methods: This cross-sectional study was conducted at the Psychiatry department of a tertiary care institution on 50 bipolar disorder patients and matched healthy controls subjects who fulfilled the inclusion criteria. The diagnosis was made by DSM-V criteria, and symptom severity was determined by the Young Mania Rating Scale (YMRS) and the Hamilton Depression Rating Scale (HAM-D). After seeking socio-demographic details, all participants were administered the Post Graduate Institute Battery of Brain Dysfunction (PGI-BBD) to assess cognitive functioning. Data collected were subjected to suitable statistical analysis (mean, standard deviation, and chi-square test). Results: The majority of the bipolar disorder patients (54%) were under 35 years of age, were males (60%), were from the urban background (70%), and were married (82%). Bipolar disorder patients performed poorly on all domains of cognitive functioning, i.e. memory, performance and verbal intelligence, and perceptuo-motor skills. Conclusion: The present study affirmed the previous findings of wide-spread cognitive impairment in bipolar disorder patients. Prompt diagnosis and treatment are the key steps to reduce the cognitive morbidity associated with this disorder.